2011
DOI: 10.1007/s00572-011-0389-8
|View full text |Cite
|
Sign up to set email alerts
|

Edible sporocarp production by age class in a Scots pine stand in Northern Spain

Abstract: With the aim of increasing knowledge of community structure, dynamics and production of ectomycorrhizal fungi, edible sporocarp yields were monitored between 1995 and 2004 in a Pinus sylvestris stand in the northeast zone of the Iberian Peninsula. A random sampling design was performed by stand age class according to the forest management plan: 0-15, 16-30, 31-50, 51-70 and over 71-years-old. Eighteen 150 m plots were established and sampled weekly every year from September to December. One hundred and ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 29 publications
3
27
0
3
Order By: Relevance
“…So, increases in the mean temperature in the different sites where it is assumed that these mushrooms have been picked would increase the amount of mushrooms placed on sale. The literature presents cases in which this hypothesis is confirmed [26], but in the particular case of the saffron milk cap, some studies done in Spain do not show any significant relationship between the yield of this mushroom and temperature [39], except that the arrival of the winter frosts limits their yield [50]. Other authors have found correlations among mushroom yields and temperatures, although the sign of the correlations, whether positive [51] or negative [52], is not clear.…”
Section: Discussionmentioning
confidence: 97%
“…So, increases in the mean temperature in the different sites where it is assumed that these mushrooms have been picked would increase the amount of mushrooms placed on sale. The literature presents cases in which this hypothesis is confirmed [26], but in the particular case of the saffron milk cap, some studies done in Spain do not show any significant relationship between the yield of this mushroom and temperature [39], except that the arrival of the winter frosts limits their yield [50]. Other authors have found correlations among mushroom yields and temperatures, although the sign of the correlations, whether positive [51] or negative [52], is not clear.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the advances of the modeling process, high variability of mushroom yields, affected mainly by weather conditions (Martínez-Peña et al, 2012a, 2012b restricts the use of sporocarp yields as a good indicator for observing the effect of changes in fungal patterns occurring in the ecosystems. Our results are a first step for using a new dependent variable to model this process.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall and temperature are critical, but their timing also appears as a crucial variable, and there is substantial annual variation in these and other climatic factors (Martínez de Aragón et al, 2007;Büntgen et al, 2015;Alfranca et al, 2015). Site factors, such as soil characteristics, altitude, slope or aspect and stand structure, including forest vegetation, stand age or stand density will also influence mushroom species richness and abundance (Martínez-Peña et al, 2012a, 2012b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mushroom production has been estimated by performing a random sampling per stand-age class according to the forest's management [17] from 1995-2013 in trough areas of Pinar Grande Forest (Figure 3). Sampling was performed in the most productive season (autumn) on a weekly basis from weeks 35-50 every year.…”
Section: Criteria Consideredmentioning
confidence: 99%